KUALITAS LAYANAN PENDIDIKAN BAGI ANAK BERKEBUTUHAN KHUSUS (ABK) DI SDN INKLUSI BANJANG 2 KECAMATAN BANJANG KABUPATEN HULU SUNGAI UTARA - Mujahadah , Siti; Riduan , Akhmad (Al Iidara Balad, 2020)
Education is the right of all citizens. Therefore, it is the state's obligation to provide adequate educational facilities and infrastructure, including in inclusive educational institutions such as SDN Inclusi Banjang 2. Even so, a number of facilities and infrastructure in this school are indicated to be inadequate so that the learning process does not go well. This research is based on a qualitative descriptive research method in which data collection is carried out through observation, interviews, and documentation study. The data obtained were analyzed using data reduction techniques, data presentation, and verification / drawing conclusions. To strive for the validity of the data, a data credibility test was taken which included extension of observations, increasing persistence, triangulation, analysis of negative cases, using reference materials, and conducting member checks. The results showed that in SDN Inclusi Banjang 2, the quality of education services has not been implemented properly. First, in terms of physical evidence, the provision of facilities and infrastructure as well as human resources has not run well where the facilities and infrastructure including practical / supporting equipment are inadequate apart from the limitations of special inclusive teachers, some irrelevant teachers' educational backgrounds, school administrative staff no and not yet available the required experts. Second, in terms of reliability, the availability of curriculum tools and work procedures is not good where in the application of the learning curriculum there is still no modification of the curriculum optimally besides the lack of a system of coordination and collaboration between the principal, teachers and school administrative staff, mentoring programs, and special service assistance to ABK. Third, in terms of responsiveness, from fast and precise service and responsiveness in service is not good where some teachers are still not careful in identifying students in order to know their backgrounds and needs in addition to curriculum design that is in accordance with the diversity of potentials and conditions of students not supported by adequate teaching materials. Fourth, in terms of assurance, the ability to generate customer confidence and courtesy is good, where in the learning process the teacher is responsible for providing assurance in service without discrimination, supported by teachers and school administrative staff who speak polite words to students. Fifth, in terms of empathy, friendly attitude and the ability to understand the desires/needs of students, both teachers and students, parents and the community as well as students in the learning process have been given attention. In the future, it is suggested to the Head of the local Education Office to carry out intensive monitoring and evaluation, provision of adequate facilities and infrastructure, training/workshops/workshops for teachers/school administrative staff, and recruitment of teachers. The principal of SDN Banjang 2 should be able to build communication with outsiders and actively provide motivation and direction to teachers/school administrative staff. Teachers/school administrative staff should be able to collaborate creatively in providing teaching materials. As for parents who have ABK, they should be actively involved in communicating with the school apart from providing support and motivation to their children.